CLEC4F Is an Inducible C-Type Lectin in F4/80-Positive Cells and Is Involved in Alpha-Galactosylceramide Presentation in Liver - Yang, Chih-Ya; Chen, Jiun-Bo; Tsai, Ting-Fen; Tsai, Yi-Chen; Tsai, Ching-Yen; Liang, Pi-Hui; Hsu, Tsui-Ling; Wu, Chung-Yi; Netea, Mihai G.; Wong, Chi-Huey; Hsieh, Shie-Liang (PloS one, 2013)
CLEC4F, a member of C-type lectin, was first purified from rat liver extract with high binding affinity to fucose, galactose (Gal), N-acetylgalactosamine (GalNAc), and un-sialylated glucosphingolipids with GalNAc or Gal terminus. However, the biological functions of CLEC4F have not been elucidated. To address this question, we examined the expression and distribution of murine CLEC4F, determined its binding specificity by glycan array, and investigated its function using CLEC4F knockout (Clec4f-/-) mice. We found that CLEC4F is a heavily glycosylated membrane protein co-expressed with F4/80 on Kupffer cells. In contrast to F4/80, CLEC4F is detectable in fetal livers at embryonic day 11.5 (E11.5) but not in yolk sac, suggesting the expression of CLEC4F is induced as cells migrate from yolk cells to the liver. Even though CLEC4F is not detectable in tissues outside liver, both residential Kupffer cells and infiltrating mononuclear cells surrounding liver abscesses are CLEC4F-positive upon Listeria monocytogenes (L. monocytogenes) infection. While CLEC4F has strong binding to Gal and GalNAc, terminal fucosylation inhibits CLEC4F recognition to several glycans such as Fucosyl GM1, Globo H, Bb3∼4 and other fucosyl-glycans. Moreover, CLEC4F interacts with alpha-galactosylceramide (α-GalCer) in a calcium-dependent manner and participates in the presentation of α-GalCer to natural killer T (NKT) cells. This suggests that CLEC4F is a C-type lectin with diverse binding specificity expressed on residential Kupffer cells and infiltrating monocytes in the liver, and may play an important role to modulate glycolipids presentation on Kupffer cells.